2007
DOI: 10.1007/s10552-007-9033-5
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors of cancer survivors: data from an Australian population-based survey

Abstract: Given their increased risk of second cancers and co-morbid chronic conditions, the lack of difference in behavioral risk factors confirms the need for a focus on improving the health behaviors of cancer survivors. Collaborative chronic disease management models may be particularly appropriate in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
173
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(202 citation statements)
references
References 35 publications
20
173
9
Order By: Relevance
“…Dietary and alcohol intakes of cancer survivors have received increasing attention in the last decade 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Overall, these studies tended to suggest an improvement in dietary behavior after cancer diagnosis, as well as a strong motivation of cancer survivors to make lifestyle changes 4.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary and alcohol intakes of cancer survivors have received increasing attention in the last decade 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Overall, these studies tended to suggest an improvement in dietary behavior after cancer diagnosis, as well as a strong motivation of cancer survivors to make lifestyle changes 4.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited empirical evidence regarding the long term health and wellbeing of cancer survivors, and even less information regarding health care needs and health service utilisation. The few international studies available [3][4][5][6][7][8][9][10] suggest that cancer survivors experience poorer health and wellbeing and have a higher level of health service utilization compared to the general population. These studies however are limited methodologically and there are no studies that have been undertaken in Northern Ireland or in the Republic of Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…47 Other factors associated with bone loss and fracture It has been reported that men with prostate cancer are more likely to be sedentary or less physically active than those without cancer. 56 Bone-loading activities are integral to stimulate positive changes in bone metabolism and conversely if the skeletal system is not subjected to weight-bearing activity bone loss occurs. 57 In addition, physical inactivity also leads to loss of muscle tissue (known as sarcopenia).…”
Section: Osteoporosis and Fractures During And Following Astmentioning
confidence: 99%